High time for a higher‐level look at high‐technology: Plotting a course for managing government information in an age of governance. (8th June 2022) - Exmeyer, Patrick C.; Hall, Jeremy L.
Abstract: For years, scholarly interest in the intersection of government and technology has overwhelmingly focused on the end‐product of technology capabilities. Recent advancements in computational power have facilitated breathtaking growth of data analytics, artificial intelligence (AI), and process automation, sparking considerable attention by scholars and practitioners alike. However, insight concerning the technology hardware assets powering emergent applications in the public sector remains glaringly absent amidst this rapidly expanding area of research. We position that gaining a greater understanding of the scope of technology utility in governance requires exploration of not only the applications or interfaces produced by technology hardware, but rather the aim of promoting both modernity and processing capacity of the hardware driving technology in government.